The Materials Science of Semiconductors - Rockett, Angus; SpringerLink (Online service) (Boston, MA : Springer US, 2008)
The Materials Science of Semiconductors serves as a general textbook on semiconductors, and discusses semiconductors in detail, from the fundamental basis for their electronic structure to engineering of alloys and the effects of defects. Written for graduate and advanced undergraduate students in the hard sciences, this book covers the materials science of semiconductors rather than focusing on electronic devices as a primary topic. The Materials Science of Semiconductors is focused on classical concepts of materials physics (including band theory), alloy design, defects and their physics, organic electronic materials, amorphous semiconductors, and thin film growth methods. This textbook includes a discussion of organic materials concepts and applications for light emitting and switching devices, and also covers the major methods for processing semiconductors from Czochralsky growth to atomic-layer deposition. Unlike other books on semiconductors, this book discusses how band structures are developed and gives a detailed calculation technique based on the LCAO method, without any significant reliance on a background in quantum mechanics. The Materials Science of Semiconductors is dedicated to presenting fundamental concepts in a manner that is accessible to students without a background in physics or quantum mechanics. Each chapter includes current applications, particularly in optoelectronics, along with recommended readings and homework problems.
An Environment of Challenges -- The Physics of Solids -- Overview of Electronic Devices -- Aspects of Materials Science -- Engineering Electronic Structure -- Semiconductor Alloys -- Defects in Semiconductors -- Amorphous Semiconductors -- Organic Semiconductors -- Thin Film Growth Processes -- Physical Vapor Deposition -- Chemical Vapor Deposition.
Keywords: Materials science; Condensed matter; Solid state physics; Spectroscopy; Microscopy; Electronics; Microelectronics; Optical materials; Electronic materials; Materials Science; Optical and Electronic Materials; Condensed Matter Physics; Solid State Physics; Spectroscopy and Microscopy; Electronics and Microelectronics, Instrumentation; Electronic books